Perkembangan Perikatan dalam Kontrak Bisnis Ditinjau dari Perspektif Hukum Indonesia - Putry Delsa Hasanah; Rival Febriyana; Nur Cahya (Program Studi Ilmu Hukum, Universitas Kuningan, 2024)
This article examines the changes in business contract obligations from a legal perspective in Indonesia. As a key component of business contracts, obligations have undergone various transformations due to regulatory developments, economic shifts, and technological advancements. This research aims to evaluate the impact of regulatory changes on the evolution of obligations and identify the factors influencing the dynamics of obligations in business contracts in Indonesia. Using a normative juridical analysis method, the article explores the application of legal principles of obligations in business practices in Indonesia. Additionally, this research addresses the legal challenges that arise in the execution of business contracts and compares the development of obligations in Indonesia with several other countries. The findings of this study reveal that adaptation to new regulations and technological innovation are crucial factors in the development of business contract obligations in Indonesia.